Genetic Diversity and Distribution of Vitamin D Receptor (VDR) Genotypes in Breast Cancer Cases from Pakistan - Faiz, Mariam; Younus, Amna; Yasmeen, Abida (Asian Pacific Journal of Cancer Biology, 2021)
Background: Breast carcinoma is one of the most commonly diagnosed invasive malignancies in females. In Pakistan, it is more commonly detected in women at a young age as compared to the West. Among all women, the risk of developing breast cancer is equal irrespective of their ethnic or racial basis. The aim of the study was to determine vitamin D receptor gene polymorphisms (FokI and TaqI) and allele frequency distribution in Pakistani women with newly diagnosed breast cancer. This study also aimed to find and compare genetic diversity of VDR polymorphisms among breast cancer cases in different population groups. Methods: Newly diagnosed women having breast cancer (n=300) were selected for the study. Blood samples of all the participants were analyzed for vitamin D levels and isolated DNA was subjected to PCR-RFLP analysis. Results: Results revealed that allelic frequency of FokI and TaqI was ‘F’; ‘f’ 50.67 and 49.33% and ‘T’ and ‘t’ was 46.67 and 53.33 respectively in Pakistani women with breast cancer. The genotypic frequency is significantly (P<0.05) distributed. Conclusion: The current study concluded significant difference in genotypes and allele frequency of VDR gene polymorphism in Pakistani population suffering from breast cancer when compared with other population.